Electronic Health Records: A Valuable Tool for Dental School Strategic Planning. Issue 5 (24th August 2018) - Filker, Phyllis J.; Cook, Nicole; Kodish‐Stav, Jodi
Abstract : The objective of this study was to investigate if electronic patient records have utility in dental school strategic planning. Electronic health records (EHRs) have been used by all predoctoral students and faculty members at Nova Southeastern University's College of Dental Medicine (NSU‐CDM) since 2006. The study analyzed patient demographic and caries risk assessment data from October 2006 to May 2011 extracted from the axiUm EHR database. The purpose was to determine if there was a relationship between high oral health care needs and patient demographics, including gender, age, and median income of the zip code where they reside in order to support dental school strategic planning including the locations of future satellite clinics. The results showed that about 51 percent of patients serviced by the Broward County‐based NSU‐CDM oral health care facilities have high oral health care needs and that about 60 percent of this population resides in zip codes where the average income is below the median income for the county (41, 691). The results suggest that EHR data can be used adjunctively by dental schools when proposing potential sites for satellite clinics and planning for future oral health care programming.